Comparing determinants of alien bird impacts across two continents: implications for risk assessment and management. Issue 14 (23rd June 2014) - Evans, Thomas; Kumschick, Sabrina; Dyer, Ellie; Blackburn, Tim
Abstract Invasive alien species can have serious adverse impacts on both the environment and the economy. Being able to predict the impacts of an alien species could assist in preventing or reducing these impacts. This study aimed to establish whether there are any life history traits consistently correlated with the impacts of alien birds across two continents, Europe and Australia, as a first step toward identifying life history traits that may have the potential to be adopted as predictors of alien bird impacts. A recently established impact scoring system was used in combination with a literature review to allocate impact scores to alien bird species with self‐sustaining populations in Australia. These scores were then tested for correlation with a series of life history traits. The results were compared to data from a previous study in Europe, undertaken using the same methodology, in order to establish whether there are any life history traits consistently correlated with impact across both continents. Habitat generalism was the only life history trait found to be consistently correlated with impact in both Europe and Australia. This trait shows promise as a potential predictor of alien bird impacts. The results support the findings of previous studies in this field, and could be used to inform decisions regarding the prevention and management of future invasions.